H. A. Rahman's Political Communication Style in Winning the 2024 Bima Mayoral Election - Ashadir, Ashadir; Ahmad, Syarif; Hidayatullah, Arief (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the political communication style of H. A. Rahman (Aji Man) in winning the 2024 Bima Mayoral Election through the dramaturgical theory of Erving Goffman, which includes three dimensions: front stage, back stage, and off stage. This research employs a descriptive qualitative method with data collection techniques such as in-depth interviews, literature review, and participatory observation. The results of the study show that on the front stage, Aji Man presents himself as a firm, articulate, and well-groomed leader to build a positive image in the public eye. In the back stage, he demonstrates strong leadership, managerial skills, and well-prepared communication strategies together with his campaign team and political party. Meanwhile, in the off stage, he appears as a humble, humorous, and approachable individual who maintains close relationships with the community, his family, and political colleagues—creating an authentic and down-to-earth impression. These three communication dimensions synergistically shape a well-rounded political image and contribute to his success in winning the election. The findings confirm that effective political communication requires a comprehensive strategy that not only focuses on public image-building but also on internal management and strong interpersonal relationships.